2013
DOI: 10.1371/journal.pone.0063155
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Genome Dynamics Revealed from Gene Distribution among the Ralstonia solanacearum Species

Abstract: Because it is suspected that gene content may partly explain host adaptation and ecology of pathogenic bacteria, it is important to study factors affecting genome composition and its evolution. While recent genomic advances have revealed extremely large pan-genomes for some bacterial species, it remains difficult to predict to what extent gene pool is accessible within or transferable between populations. As genomes bear imprints of the history of the organisms, gene distribution pattern analyses should provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…By analyzing the comparative genomic hybridization on microarrays, Guidot et al (7) demonstrated that DNA blocks of 30 kb and 33 genes could be integrated during a single transformation event. Lefeuvre et al (16) reported that most of the putative HGT events were detected between strains clustered with the Molk2 strain (IIB-3) and in recombinogenic strains of phylotypes I and IIA. Moreover, a limited number of HGT events was found among strains of phylotypes I, III, and IV.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the comparative genomic hybridization on microarrays, Guidot et al (7) demonstrated that DNA blocks of 30 kb and 33 genes could be integrated during a single transformation event. Lefeuvre et al (16) reported that most of the putative HGT events were detected between strains clustered with the Molk2 strain (IIB-3) and in recombinogenic strains of phylotypes I and IIA. Moreover, a limited number of HGT events was found among strains of phylotypes I, III, and IV.…”
Section: Discussionmentioning
confidence: 99%
“…Complete genomic sequences have been determined for several strains of the R. solanacearum species complex 21 . These strains express more than 20 MCPs, including two aerotaxis sensors 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Complete genomic sequences have been generated for several strains of the R. solanacearum species complex (22). Genomic analysis revealed that these strains each encode Ͼ20 MCPs.…”
mentioning
confidence: 99%